Variation of Mineral Composition in Different Parts of Mahaleb - Sekeroglu, Nazim; Aknil Meraler, Seval; Ozkutlu, Faruk; Kulak, Muhittin (Asian Journal of Chemistry, 2012)
A wild member of Rosaceae family, Mahaleb (Prunus mahaleb L.) is a small tree or shrub with white flowers. This wild plant is important rootstock for cultivated cherry plants and its various parts are used as a spice and traditional medicine in Turkey. All the plant parts of mahaleb contain essential oil and coumarins as the major secondary metabolites. Plants capture minerals from the soil and accumulate them in different parts of their body. Mineral compositions and contents of the plants vary by different plant parts, soil properties, environmental conditions, agricultural techniques etc. Besides positive effects on plant development, accumulated minerals in used plant parts are important for human health. Some minerals such as calcium, iron and zinc are known to be useful for health and their optimum levels are desired. In contrast to them, heavy metals harmful for human health like cadmium, copper, nickel and lead-found in industrialized and urban areas- are not desired in high quantities. In recent years, studying on the mineral compositions of functional plants stands out due to their impact on human health. For this purpose, mineral composition (Al, B, Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Mo, N, Na, Ni, P, Pb, S and Zn) of distinct parts (stem, leaf, flower, fruit, kernel and resin) of mahaleb cherry were detected by ICP-AES. According to the determined results, investigated parts of mahaleb had acceptable ranges for mineral compositions.